Ion-Track Etched Templates for the High Density Growth of Nanowires of Bismuth Telluride and Bismuth Antimony Telluride by Electrodeposition. (10th February 2015) - Koukharenko, E; White, Neil; Li, X; Nandhakumar, Iris
Abstract : We report the electrochemical growth of high density arrays of n- type Bi2 Te3 and p-type Bi0.5 Sb1.5 Te3 nanowires into ion-track etched polyimide-based Kapton membranes with a density of 5 x 10 9 wires/cm 2 . The average diameter of the nanowires is 80 nm with a length of 20 μm, which is comparable to the pore size and thickness of the employed Kapton foils. The electroplating parameters and microstructural properties are reported for the nanowires whilst thermoelectric properties have been investigated for thin films of Bi2 Te3 and Bi0.5 Sb1.5 Te3 .